Mediasi Kinerja Keuangan pada Hubungan Leverage dan Likuiditas terhadap Penghindaran Pajak - Mardiana, Mardiana; Setiyowati, Supami Wahyu (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2024)
Purpose: Tax avoidance is a strategic approach aimed at reducing the tax burden while staying within the boundaries of applicable regulations. The objective of this study was to examine how leverage and liquidity influence tax avoidance, with financial performance acting as an intermediary factor. Method: The research focused on publicly listed financial sector companies on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The sample selection process adhered to specific criteria, resulting in a sample size of 38 companies. Smart PLS was employed as the data analysis technique. Results: The findings indicated that leverage had an impact on financial performance, liquidity affected financial performance, and financial performance played a role in tax avoidance. However, financial performance did not act as a mediator in the relationship between leverage, liquidity, and tax avoidance. Implications: This research can be used as material for study and evaluation for the government in relation to existing tax policies. On the other hand, it is expected to increase compliance and awareness of the company in fulfilling its tax obligations. Novelty: This research uses profitability mediation in the relationship between leverage, liquidity, and tax avoidance